Перспективи міжнародної інтегрованої звітності - Костирко, Р. О. (Видавництво Львівської політехніки, 2014)
Визначено передумови, проблеми та переваги формування інтегрованої звітності компаній. Структуровано компоненти інтегрованої звітності та надано їх характеристику. Розкрито базові концепції та зміст елементів інтегрованої звітності. Обґрунтовано перспективи реалізації концепції інтегрованої звітності. Сформовано рекомендації щодо підготовки інтегрованої звітності стійкого розвитку компаній. На основі аналізу міжнародних стандартів визначено мету, завдання та предметне поле аудиту якості інтегрованої звітності. Reveals the importance of making the basic principles of international integrated reporting, including the possibilities of transforming the economic model for the formation of an objective financial data needed to manage financial capital. Identified deficiencies modern standardized financial statements, including the alleged failure in her scorecard for social, environmental and economic development. The preconditions, problems and advantages of forming integrated reporting companies are defined. Argued proved that the methodological basis for integrated reporting should be based on the concepts of capital, including intellectual and business model with elements of the resource concept of value-based strategic management. Components of the integrated reporting are structured and its characteristic is given. Base conceptions and content of the integrated reporting is disclosed. The perspectives of implementing the concept of integrated reporting are grounded. Recommendations regarding the preparation of integrated reporting sustainable development companies are formed. According to the analysis of the international standards, goals, objectives and subject of the audit quality integrated reporting are defined.
Perspectives of integrated reporting
Keywords: підприємство; управління; інтегрована звітність; базові концепції; міжнародні стандарти; регламентації; функціональне управління; enterprise management; integrated reporting; basic concepts; international standards; regulations; functional management